ARDS Outcomes in Non-Research Subjects Assessed by Generalized Prospective Trial Eligibility Criteria and Adherence to Lung-Protective Ventilation. - Kallet, Richard H.; Lipnick, Michael S.; Pirracchio, Romain (Respiratory Care, 2021)
BACKGROUND: ARDS mortality is lower among subjects participating in randomized controlled trials (RCTs) compared to subjects in observational studies. Excluding potential subjects with inordinately high mortality risk is necessary to prevent masking the impact of potentially effective treatments. We inquired whether observed mortality differed between RCT-eligible and RCT-ineligible subjects managed with varying degrees of lung-protective ventilation in a non-research setting. METHODS: This single-center, retrospective, observational study utilized quality assurance data for monitoring lung-protective ventilation practices based upon National Institutes of Health ARDS Network (ARDSNet) protocols. Between 2002 and 2017, 1,975 subjects meeting the 1994 consensus criteria for acute lung injury/ARDS (later reclassified by the Berlin definition) were prospectively identified and classified as RCT-eligible or RCT-ineligible on the basis of the original ARDSNet exclusion criteria for comorbidities or moribund condition. Demographic and physiologic data from the day of ARDS onset and outcome data were studied. Survival was modeled with a mixed-effect Cox proportional hazard model adjusted for age, both illness and lung injury severity plateau pressure, and formal use of the ARDSNet ventilator protocol. The primary outcome of interest was all-cause mortality during the first 90 d following onset of ARDS. RESULTS: Day 90 mortality was 27.6% in RCT-eligible subjects versus 50.4% in RCT-ineligible subjects (hazard ratio 0.47 [95% CI 0.41--0.54], P < .001). Regardless of eligibility or ineligibility, achieving a plateau pressure ≤ 30 cm H2O was associated with lower mortality. Overall, mortality risk was lower in subjects managed by protocol versus clinician-directed lung-protective ventilation (hazard ratio 0.60 [95% CI 0.52--0.69], P < .001), even among those in whom plateau pressure was ≤ 30 cm H2O (hazard ratio 0.64 [95% CI 0.54--0.76], P < .001). CONCLUSIONS: Mortality in non-research, RCT-eligible subjects was substantially lower compared to RCT-ineligible subjects. Managing non-research patients with ARDS by keeping plateau pressure ≤ 30 cm H2O and formal use of a lung-protective ventilation protocol significantly reduces mortality risk.